An Analysis of the Role of Quizizz Paper Mode in Enhancing Students' English Learning Engagement and Motivation At SDN 5 Arawa - Ardiansyah Putra; Andi Sadapotto; Buhari; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examines the role of Quizizz Paper Mode an offline, printable adaptation of the gamified Quizizz platform in enhancing fifth-grade students’ engagement and motivation in English as a Foreign Language (EFL) learning at SDN 5 Arawa, a low-resource public elementary school in rural South Sulawesi, Indonesia. Amid persistent challenges of low participation and motivation in conventional paper-based EFL instruction, particularly in technology-limited settings, the research investigates whether this low-tech gamified tool can foster more interactive and motivating classroom experiences. Adopting a descriptive qualitative design, the study collected data through structured classroom observations and semi-structured interviews with five purposively selected fifth-grade students and their English teacher. Observations focused on three dimensions of engagement behavioral, emotional, and cognitive alongside indicators of intrinsic and extrinsic motivation. Interview responses provided in-depth insights into participants’ perceptions and experiences. Data were analyzed using Miles, Huberman, and Saldaña’s (2014) interactive model, with triangulation ensuring credibility. Findings revealed that Quizizz Paper Mode significantly improved all aspects of student engagement. Students exhibited greater behavioral participation and persistence, heightened emotional enthusiasm, enjoyment, and confidence, and stronger cognitive focus, effortful thinking, and strategy use. Both intrinsic motivation (interest, curiosity, and enjoyment) and extrinsic motivation (competition, scoring, and achievement orientation) increased markedly due to the tool’s game-like elements such as time limits, immediate feedback, and ranking systems. Participants and the teacher perceived the activity as more enjoyable and less anxiety-inducing than traditional assessments. The tool proved highly practical and inclusive in low-resource classrooms, requiring no internet access or personal digital devices. This research concludes that Quizizz Paper Mode is an effective, accessible, and equitable strategy for boosting engagement and motivation in primary EFL learning within resource-constrained contexts. Practical implications for teachers and recommendations for future studies are discussed.